Android TV apps development : building for media and games - Trebilcox-Ruiz, Paul (Apress, 2016)
Android TV Apps Development: Building Media and Games walks you through creating fantastic entertainment applications for one of the newest Android platforms. This book will demystify some of the newest APIs and present the tools necessary for building applications that run on Android TV. Walking through example applications, you will learn the vocabulary necessary to solve real world problems and how to present your content on the television through Android. In addition to practical code examples, you will learn about various design considerations that will make using your apps an enjoyable experience for users. What you'll learn: How to design for Android TV How to create a media app for Android TV What are the game design/development considerations for Android TV How to distribute Android TV apps.